Knowledge, attitude and perception among medical students and healthcare professionals regarding male infertility: a cross-sectional survey from Bangladesh. Issue 11 (10th November 2022) - Iktidar, Mohammad Azmain; Chowdhury, Sreshtha; Roy, Simanta; Islam, A M Khairul; Islam, Mahzabeen; Chowdhury, Tonmoy; Tabassum, Mustari Nailah; Ali, Tahsin Sumat; Akash, Atandra; Ahmed, Mashrur; Zafar, Faraz Al; Hawlader, Mohammad Delwer Hossain
Abstract : Objective: This study aimed to explore the knowledge, attitude and behaviour regarding male infertility among medical students and healthcare workers in Bangladesh. Design: This was a cross-sectional study. Setting: This study covered eight divisions of Bangladesh. Participants: The participants were medical students or healthcare professionals of Bangladesh who were surveyed anonymously on their knowledge, attitude and perception regarding male infertility. Primary outcome measures: The level of knowledge, attitude and perception regarding male infertility. Analysis: The mean knowledge and attitude scores were then correlated with sociodemographic factors using χ 2 and two-independent sample t-tests. Finally, we performed binary logistic regression to explore predictors of good knowledge and positive attitude. Result: Among 556 participants, 49.82% did not have good male infertility knowledge, and nearly 60.79% had negative attitudes regarding male infertility. Young (23–26 years) healthcare professionals and medical students were more likely to have good knowledge than others (OR: 1.81; 95% CI 1.099 to 2.988). Surprisingly, women were more likely to have a positive attitude (OR=1.48; 95% CI 1.002 to 2.19, p=0.049) than men. Among all the professions, Bachelor of Medicine and Surgery doctors were most likely to have good knowledge and a positive attitude regarding male infertility. Good knowledge of male infertility predicted a positive attitude (OR=1.61; 95% CI 1.105 to 2.346, p=0.013) and vice versa. Conclusion: Our research found that healthcare professionals and medical students in Bangladesh had inadequate knowledge and negative attitudes regarding male infertility despite favourable opinions. This emphasises the need for interdisciplinary training programmes, standardisation of healthcare worker guidelines and curricular adjustments for medical students.